Paste as a new product from Bamboo shoot (Dendrocalamus asper): physicochemical and microbiological properties (Research, Society and Development, 2021)
There are 50 to 60 bamboo species, which the shoots are edible. This work aimed for the development and characterization of a new product from the Dendrocalamus asper specie, related to physicochemical, microbiological, texture and color characterization of a bamboo shoot paste. Cyanide was eliminated through preprocessing and the formula of the new product did not compromise bamboo shoots characteristics, as low-fat content food. The presence of phenolic compounds in the paste and antioxidant activity, even considering a product of high content of moisture, supports its consumption. As to the obtaining conditions, microbiological results indicate that consumption is safe, right after the paste production and during storage. The texture characteristics during storage, at room temperature and under cold, indicate the technical viability for this product, achieving stability, although it is still nonexistent in the market. Color changes in the final product, comparing to raw material, kept typical characteristics of bamboo shoot during storage, even considering browning reactions due to thermal treatment.